2010
DOI: 10.4141/cjas10036
|View full text |Cite
|
Sign up to set email alerts
|

Serum micronutrient concentrations in beef cows before and after the summer grazing season

Abstract: Van De Weyer, L. M., Hendrick, S. and Waldner, C. L. 2010. Serum micronutrient concentrations in beef cows before and after the summer grazing season. Can. J. Anim. Sci. 90: 563Á574. Serum concentrations of Cu, Mn, Mo, Se, vitamin A, and vitamin E were measured at the start and at the end of the summer grazing season in an observational field study of 791 commercial beef cows from 40 cow-calf herds from five community pastures. Copper and vitamin A were higher in the fall (PB0.001), and Mo (P B0.001) and selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…Recent studies have indicated that copper levels are correlated with retinol levels. These results are in accordance with the findings of Van De Weyer et al (2010), who found similar deficient results in beef cows on pastures for this micronutrient.…”
Section: Resultssupporting
confidence: 93%
“…Recent studies have indicated that copper levels are correlated with retinol levels. These results are in accordance with the findings of Van De Weyer et al (2010), who found similar deficient results in beef cows on pastures for this micronutrient.…”
Section: Resultssupporting
confidence: 93%
“…; Van De Weyer et al . ). In the present study, we did not determine the intake of a‐Toc and BC from forage, but serum a‐Toc and BC levels in heifers during the grazing period were higher than those in pre‐grazing, suggesting that heifers in both FG and PG consumed higher amounts of a‐Toc and BC compared to the respective pre‐grazing amounts.…”
Section: Discussionmentioning
confidence: 97%
“…The amount of vitamin A in cows' colostrum and milk depends on their intake during late gestation. Concentrates are a poor source of vitamin A and β-carotene, and vitamin A concentrations are higher in cattle after summer grazing periods compared with after winter feeding (Puls 1994;Nozière et al 2006;Van de Weyer et al 2010). This is at least in part due to the decrease in vitamin A precursor content and biological activity that occurs due to heat, light, and moisture during harvesting for hay or silage and dehydrating in preparation for storage (McDowell 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Both vitamin A and vitamin E concentrations were lower in calves from heifers than in calves born to cows. Although heifers may have lower volume and quality of colostrum, this relationship is not immediately intuitive, and in fact, a number of studies have demonstrated that the serum vitamin A, vitamin E, and β-carotene concentrations in older cows were lower compared with younger cows (Katsoulos et al 2005;van de Weyer et al 2010). Similarly, calves from heifers had higher liver vitamin A concentrations compared with calves from cows in a study on micronutrient concentrations in beef calves that had died (Waldner and Blakley 2014).…”
mentioning
confidence: 99%